Chapter 3: Microlevel information and policy implications - von Braun, Joachim; Pandya-Lorch, Rajul (International Food Policy Research Institute, 1991)
This research is stimulated by the preliminary insight that rural households, even if they are poor and/or located in so-called subsistence-oriented regions, are dependent on a variety of farm, nonfarm, and nonagricultural income sources. The scale and nature of these income sources and their relationship to the major economic sectors (agriculture, rural manufacturing, and services), through backward and forward linkages, need to be better understood for priority setting in development policy. The objectives of this study are threefold:; 1) to identify employment and income sources of rural households of different socioeconomic characteristics in regions and countries at different stages of agricultural transformation and development; 2) to trace income and employment strategies (as revealed by these) of rural households, and, thus, to broaden the information base for policy priorities for integration of the poor into a sustainable growth and development process.; 3) to look into distributions below and above the poverty line in order to identify relevant differences in demographic, income, and employment characteristics of poor and nonpoor rural households and, thereby, assess the scope for targeting" income sources of the poor as a poverty alleviation strategy.; Poverty is essentially, but not always, a matter of low incomes, where the cost of acquiring a certain commodity bundle determines the income- or expenditure-based poverty line. An income-based indicator is an indirect means of measuring poverty. In this study, poverty is measured directly through consumption, given certain commodity characteristics and behaviors, rather than in directly through incomes. A central and fundamental characteristic of absolute poverty is insufficient food consumption for an active and healthy life. The poverty line (cutoff point) is defined here by calorie consumption being 80 percent of the recommended consumption for an active and healthy life." from authors' abstract